Gallic Acid-Dextran Conjugate: Green Synthesis of a Novel Antioxidant Molecule - Moacir Fernandes Queiroz; Diego Araujo Sabry; Guilherme Lanzi Sassaki; Hugo Alexandre Oliveira Rocha; Leandro Silva Costa (MDPI AG, 2019)
A novel derivative of dextran, dextran−gallic acid (Dex−Gal), obtained from simple conjugation with gallic acid, was synthesized by an efficient free radical-mediated method. To verify the synthesis of Dex−Gal, 1H-nuclear magnetic resonance (1H-NMR), Fourier transform infrared (FTIR) spectrometry, and high-performance size-exclusion chromatography (HPSEC) were employed. The results revealed the conjugation of gallic acid with the 15.5 kDa dextran from Leuconostoc mesenteroides. Dex−Gal had a molecular weight of 11.2 kDa, indicating that the conjugation reaction was accompanied by a minor degradation of Dex−Gal. In addition, Dex−Gal contained 36.8 ± 1.4 mg gallic acid per gram dextran. These molecules were also evaluated as antioxidants using total antioxidant capacity (TAC), reducing power, ferric chelation, and superoxide radical-scavenging assays. Both polysaccharides had no ferric chelation activity. In addition, Dex−Gal was more efficient as an antioxidant agent in TAC (13 times) and was more efficient than dextran in superoxide radical-scavenging (60 times) and reducing power (90 times) assays. These data demonstrate that Dex−Gal is a natural-compound-based antioxidant with potential applications in the pharmaceutical, cosmetic, and food industries.